Accuracy of frozen section analysis in correlation with surgical pathology diagnosis - Patil, Parikshit; Shukla, Samarth; Bhake, Arvind; Hiwale, Kishore (International Journal of Research in Medical Sciences, 2017)
Background: Intra-operative consultation by frozen section is a high risk procedure with important consequences. Therefore it is critical to determine efficiency of frozen section performance periodically. This study was performed to determine accuracy of frozen section. Methods: In this prospective study, we compared the results of 100 consecutive cases of frozen section with their final permanent section diagnosis in a teaching hospital of Jawaharlal Nehru Medical College, Wardha, Maharashtra during July 2012 to June 2014. Results: A total of 100 cases were studied on frozen section while one case was deferred for permanent paraffin section (deferral rate 01%). The overall accuracy of frozen section was 96.96% with false positive and false negative rates of 1.01% and 2.02% respectively. Sensitivity, specificity, positive predictive value and negative predictive value were 97.22%, 96.30%, 98.59% and 92.86% respectively. The turn-around time of 18 minutes was observed in the present study. Conclusions: The accuracy of frozen section diagnosis at our institute can be interpreted as comparable with most international quality control statistics for frozen sections. The overall error rate and deferral rates are within the range previously published studies. The results suggest specific measures should be taken to reduce the number of discrepancies.